Mental health in disaster situations - León-Amenero, Deborah (2019)
Disasters are large-scale events which are often unexpected. Usually more attention is paid to the material and physical consequences of disasters. However, interventions in disaster situations are incomplete if mental health issues are not addressed. This work aims to review the psychosocial consequences associated with a disaster, including mental health problems such as post-traumatic stress disorders, depressive disorders, psychoactive substance abuse, etc., and the psychosocial consequences in the family structure, highlighting the possible risk factors related to their presentation. The intervention strategies are varied and depend on the time, the person and the level of action. It is necessary that we, as a country, have different intervention strategies and models to try to mitigate the psychosocial impact of disasters. Nevertheless, there continue to be barriers in the management of mental health, so it is necessary to consider possible future directions in order to achieve a lower impact on society and an earlier recovery.